Franklin and Luna go to the moon - Campbell, Jen.; Harnett, Katie (London : Thames and Hudson, 2018)
Luna and her bestfriend, Franklin the dragon, love stories and want to visit all the places they've read about in books. Along the way, they meet many magical creatures but there's just one problem- they can't remember where dragons live! They search high and low, but to no avail until, one evening, Luna's tortoise, Neil Armstrong, notices something moving far away in the sky... Together they set out on their biggest adventure yet- all the way to the moon! - in the ope of finding Franklin's lost family.
Keywords: Dragons -- Pictorial works -- Juvenile fiction. -- Friendship -- Pictorial works -- Juvenile fiction. -- Families -- Pictorial works -- Juvenile fiction